2021
DOI: 10.3390/antibiotics10091093
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Levels of Toxin A Correlate with Disease Severity in Patients with Clostridioides difficile Infection

Abstract: Cloistridioides difficile (CD) represents a major public healthcare-associated infection causing significant morbidity and mortality. The pathogenic effects of CD are mainly caused by the release of two exotoxins into the intestine: toxin A (TcdA) and toxin B (TcdB). CD infection (CDI) can also cause toxemia, explaining the systemic complications of life-threatening cases. Currently, there is a lack of sensitive assays to detect exotoxins circulating in the blood. Here, we report a new semi-quantitative diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…They also observed toxemia in 33 out of 35 patients studied, indicating a high prevalence of toxins in the bloodstream. This suggests a potential association between elevated serum TcdA levels and the development of severe complications in CDI cases [183].…”
Section: Toxemia and Extraintestinal Damage Caused By Tcda And Tcdbmentioning
confidence: 93%
“…They also observed toxemia in 33 out of 35 patients studied, indicating a high prevalence of toxins in the bloodstream. This suggests a potential association between elevated serum TcdA levels and the development of severe complications in CDI cases [183].…”
Section: Toxemia and Extraintestinal Damage Caused By Tcda And Tcdbmentioning
confidence: 93%
“…Toxigenic strains may produce both toxin A and toxin B (causing the majority of CDIs), TcdB alone (A−B+strains), or TcdA alone (A+B−strains) [ 58 , 59 , 60 , 61 ]. Recent research proves the positive correlation between high serum levels of toxin A and the severity of CDI [ 62 ]. Toxemia could explain systemic clinical manifestations in severe cases of CDI [ 63 , 64 ].…”
Section: Pathogenic Mechanismsmentioning
confidence: 99%
“…Regarding CDI pathogenesis, the work by Di Masi et al presented a novel semiquantitative diagnostic method to measure the serum levels of CD toxins, i.e., toxin A and toxin B [12]. By the use of this new assay, the authors report the detection of toxemia in 33 out of the 35 CDI cases included in the study.…”
mentioning
confidence: 99%
“…By the use of this new assay, the authors report the detection of toxemia in 33 out of the 35 CDI cases included in the study. The relationship between toxin A serum levels and CDI severity was also assessed, reporting that, at the time of CDI diagnosis, the proportion of severe CDI cases with a toxin A serum level >60 pg/µL was higher than in mild CDI cases (29.4% versus 66.6%, p = 0.04) [12]. Of interest, this study showed that toxemia is much more frequent than expected in CDI patients, and that high serum levels of toxin A correlate with CDI severity [12].…”
mentioning
confidence: 99%